PREPOSISI AUF BAHASA JERMAN DAN PENGUNGKAPAN MAKNANYA DALAM BAHASA INDONESIA - syahid, Agus (LPPM Universitas Bumigora Mataram, 2018)
This research is trying to describe about auf as a preposition. The aim of this research to describe the meaning of auf as a preposition and then trying to describe the equivalent meaning in Indonesian. Theories which are used in this research are the theory of Gouvernment-Binding (GB) in order to describe the auf as a preposition related with the case which causes by the auf preposition. The method of this research is a descriptive analysis method. Data in this research is written and oral data (taken from the informan). The written data is taken from several novels using German language and German dictionary. The oral data is taken from three native German university students which are used to support the data. The result of this research shows that the auf preposition in German language which has meaning as a propositional to describe a space can influence accusative and dative cases. The prepositional auf can control the accusative case in pointing a direction (Richtung), in describing a movement (Bewegung) and describing a goal (goal). The auf preposition which has accusative case is expressed by the preposition of ke in Indonesian language. The auf preposition can also control the dative case if it is describes a situation or position in some place. The description of auf preposition with dative case is expressed by the preposition of di in Indonesian language.